Bagaimana Mengukur Happiness at Work? (Studi Pada Karyawan Perusahaan ITDC – Injourney Tourism Development Corporation) - Muhammad Berwyn Tristan Athalla; Andriyani Andriyani (Faculty of Economics and Business Diponegoro University, 2025)
This study aims to analyze the factors that influence employee happiness at work and its impact on the organization. This study explores employee happiness levels at InJourney Tourism Development Corporation. From a population of 193 employees, a sample of 158 was selected using purposive sampling.Data were analyzed using exploratory factor analysis (EFA) and confirmatory factor analysis (CFA). Reliability and validity analysis showed strong results, with Cronbach’s Alpha values ≥ 0.9 and adequate convergent and discriminant validity.Employee happiness was found to be influenced by work engagement, job satisfaction, and affective commitment, which play a crucial role in fostering a supportive work environment. This study highlights the importance of managing employee happiness to enhance well-being and achieve long-term organizational success